Migration and the reconfiguration of rural places: the accommodation of difference in Odemira, Portugal - Fonseca, Maria Lucinda (2021)
International migration reconfigures rural places by engaging localities with globalising forces. Accommodating newcomers, be they farming labourers or lifestyle migrants is a challenge at the local level due to the clash of interests, different visions on how the land should be managed and development promoted. Using Odemira as a case study, the paper has two goals: to show the change brought about by foreign investments in agribusiness, international labourers and lifestyle migrants to a rural place; and to highlight the strategies devised by local actors in the accommodation of new demands of language and housing. Language classes for adults and housing provisions are far from satisfying the needs. Schools display more flexibility to accommodate migrant children, whereas the agribusiness firms are increasing its lobbying capacity for their interest by pushing forward the approval of an exceptional regime that authorises the installation of workers in precarious accommodation located on the farms.